Bioassay guided isolation and characterization of compounds with antioxidant activities from the leaves of Entada spiralis Ridl. (Sintok) - Sharifah Nurul Akilah binti Syed Mohamad (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2017)
Entada spiralis Ridl. known as Sintok or Akar Beluru is the woody climber plant belong to Leguminoceae family. E. spiralis is an excellent foaming agent due to the presence of saponin. Thus, E. spiralis stem bark is established used as natural body soap, shampoo and washing agent. The possession of antioxidant activity has been revealed by E. spiralis ability to treat syphilis, insect bites and superficial skin diseases. This research aims to screen the major compounds by phytochemical screening test, verify the antioxidant compounds from crude extracts and fractions via in-vitro antioxidant activity assays, isolate the antioxidant compounds through chromatographic methods and characterize the structure of antioxidant compounds by using various spectroscopic techniques. The crude extract of E. spiralis leaves was prepared by macerating the leaves with petroleum ether, chloroform, and methanol solvent sequentially. Determination and evaluation of antioxidant activity was done through in-vitro study by using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical, and 2,2-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical cation. Folin-Ciocalteu's reagent method was used to measure total phenolic content and flavonoid content was evaluated by calorimetric method. The crude extract of E. spiralis leaves was fractionate by vacuum liquid chromatography (VLC) and liquid-liquid extraction. Isolation of antioxidant compounds was further with column chromatography technique and characterized by spectroscopic analysis. Methanol, chloroform, and petroleum ether crude extracts were analyzed with 5.53 %, 2.05 % and 2.55 % yield. Saponin and flavonoid were the major components. Methanol extract exhibited the highest antioxidant activity with IC50 (DPPH); 40.23 ± 2.66 ug/mL and IC50 (ABTS); 5.09 ± 0.53 ug/mL. The highest possession of phenolic content and flavonoid content; 124.67 ± 6.63 mg GAE/g and 51.67 ± 2.17 mg QE/g were also displayed by the methanol extract. Isoscutellarein, kaempferol-3-C-rutinoside, kaempferol-3-O-glucoside, and kaempferol glycoside were isolated from liquid–liquid extraction fraction while stearic acid and ethyl oleate were isolated from the fraction of vacuum liquid chromatography. IC50 (DPPH) of isoscutellarein; 112.18 ± 2.21 ug/mL, kaempferol-3-C-rutinoside; 136.04 ± 0.52 ug/mL, kaempferol-3-O-glucoside; 301.01 ± 3.02 ug/mL, and stearic acid; 187.49 ± 1.37 ug/mL. Ethyl oleate and kaempferol glycoside were showed negative results towards DPPH. Whereas, IC50 (ABTS) of isoscutellarein; 17.50 ± 0.26 ug/mL, kaempferol-3-C-rutinoside; 34.10 ± 1.13 ug/mL, kaempferol-3-O-glucoside; 14.65 ± 0.11 ug/mL, stearic acid; 5.69 ± 0.06 ug/mL, ethyl oleate; 474.37 ± 2.91 ug/mL, and kaempferol glycoside; 124.82 ± 6.60 ug/mL. In conclusion, the active crude extract and fraction was verified by several in-vitro antioxidant assays. Six antioxidant compounds were successfully isolated from this research study.